TINJAUAN SADD AL-DZARI’AH TERHADAP DAMPAK NEGATIF NIKAH SIRRI - Azizah, Nur; Pandabo, Gizka Triana; Gunawan, Edi (IAIN TERNATE, 2024)
Sirri marriage is a marriage that is performed according to their respective religions and beliefs without registering a marrrfiage by the Registrar ofMarriages. Sirri marriages carried out by Islamic religious societies that meet thepillars and conditions are basically valid, but become problematic when one ofthe family members or spouses commits a marriage violation. In Girian Subdistrict, there are several wives who hold a second marriage while the first marriage has not been completed or has not been completed, so there is a polyandry marriage. This happens because the business is done in a sirri manner.The study used the sadd al dzari'ah method to analyze the phenomenon of sirri marriage that occurred in Girian District by considering mafsadat. This research uses an empirical juridical approach with the type of field research